Beyond species richness and community composition: Using plant functional diversity to measure restoration success in jarrah forest. Issue 3 (9th September 2021) - Standish, Rachel Jayne; Gove, Aaron David; Grigg, Andrew Haden; Daws, Matthew Ian
Abstract: Aim: The importance of restoring ecosystem functions to native systems that have been degraded, damaged or destroyed is increasingly recognised. Yet few studies have measured the effect of restoration efforts on ecosystem functioning or the functional diversity (FD) that underpins it. Here we assessed change in FD of restored assemblages one to 25 years after the onset of post‐mine restoration. Location: Northern Jarrah ( Eucalyptus marginata Donn ex Sm.) Forest bioregion of southwestern Australia. Methods: Functional richness, evenness, divergence and dispersion were derived from five plant functional traits relevant to community reassembly. Effects of three explanatory variables (i.e. age, year restoration was initiated, and time since fire) on six response variables (i.e. four FD indices, species richness, and compositional similarity to nearby reference forest) were analysed using linear mixed models for a data set with repeated measures of plots through time ( n = 810 plots), and linear models for a subset of one‐time measures of different aged assemblages (i.e. space‐for‐time approach; n = 490 plots). Results: Functional evenness and functional dispersion increased with age, while functional divergence and functional richness decreased with age. Functional dispersion increased with time since fire, while functional richness decreased with time since fire. Species richness decreased with age, but at 25 years, species richness was comparable to that observed in reference forest. In contrast, similarity showed no relationship with age of restored forest, and at 25 years, similarity of restored forest to reference was low compared with similarity of reference forest to itself. Three of four FD indices had not reached those of reference jarrah forest 25 years after restoration had been initiated. Conclusions: Reassembly of FD suggests importance of environmental filtering and high functional redundancy. A longer time frame may be needed to assess FD of restored assemblages, and in the meantime, species richness is not an adequate surrogate of FD. Abstract : FD is a critical component of restoration success yet rarely measured. We found that functional evenness and functional dispersion increased with age but not to levels in reference jarrah forest after 25 years. Species richness had recovered by 25 years but did not correlate with any of the four FD indices.